American Presidents and Israeli Settlements since 1967. - Cairo, Michael F., 1970- ([Place of publication not identified] : Routledge, 2022)
Tracing presidential administrations since Lyndon B. Johnson, this book argues that the Trump administration's policy toward Israeli settlements in the West Bank and Jerusalem is not an aberration but the culmination of over 50 years of American foreign policy. Under the Johnson administration, the United States rhetorically supported the applicability of international law regarding Israeli settlements. However, throughout the 1970s, administrations did little to reverse the construction and expansion of settlements. Moreover, presidents sent mixed signals regarding Israel's withdrawal from the occupied territories. The Israeli settlement movement received support when Reagan argued that settlements were not illegal. Since then, American presidents have opposed settlement activity to various degrees, but not based on their illegality. Rather, presidents have described them as unwise, unhelpful, or obstacles to peace. Even when presidents have had opportunities to confront Israeli settlements directly, domestic pressure and America's special relationship with Israel have prevented serious action beyond rhetoric and condemnation. This volume will be of interest to scholars and students of the history and politics of American foreign policy, American relations with Israel, and the Israeli-Palestinian conflict.
1. Introduction 2. Lyndon B. Johnson and the Problem of Territorial Integrity3. Nixon, Ford, and Kissinger: Limited Withdrawal 4. Jimmy Carter and the Illegality of Israeli Settlements5. Reagan and Bush 41: Not Illegal But a "Real Problem" 6. Bill Clinton: "Complicating Factors7. George W. Bush: From "Anything But Clinton" to More of the Same 8. Barack Obama's Failed Expectations 9. Settled
Keywords: POLITICAL SCIENCE / General; Land settlement -- Government policy -- Israel; Arab-Israeli conflict; Presidents -- United States -- History; United States -- Foreign relations -- Israel; Israel -- Foreign relations -- United States; United States -- Foreign relations -- 1945-1989.; United States -- Foreign relations -- 1989-